2013
DOI: 10.5194/acpd-13-28395-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The 2013 severe haze over the southern Hebei, China: model evaluation, source apportionment, and policy implications

Abstract: Abstract. Extremely severe and persistent haze occurred in January 2013 over the eastern and northern China. The record-breaking high concentrations of fine particulate matter (PM2.5) of more than 700 μg m−3 on hourly average and the persistence of the episodes have raised widespread, considerable public concerns. During that period, seven of the top ten polluted cities in China were within Hebei Province. The three cities in southern Hebei, Shijiazhuang, Xingtai, and Handan, have been listed as the top three … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 56 publications
2
63
0
1
Order By: Relevance
“…The high uncertainty of emission inventories and meteorological simulation results affected the accuracy of the air pollution simulation results. A previous study also showed a large bias during heavily polluted days, which is an inherent characteristic that the model can produce [39]. According to the U.S. Environmental Protection Agency [38], all parameters followed the guidelines, and the WRF-Chem model predicted variables reasonably well in this work.…”
Section: Model Performancesupporting
confidence: 60%
“…The high uncertainty of emission inventories and meteorological simulation results affected the accuracy of the air pollution simulation results. A previous study also showed a large bias during heavily polluted days, which is an inherent characteristic that the model can produce [39]. According to the U.S. Environmental Protection Agency [38], all parameters followed the guidelines, and the WRF-Chem model predicted variables reasonably well in this work.…”
Section: Model Performancesupporting
confidence: 60%
“…Besides our direct visualization, model simulations also supported regional transport as a significant resource of smog episodes. In this study, however, the ground monitor data collected from the same source of our study was only used for evaluating of the simulation results of Mesoscale Modeling System Generation 5 (MM5) and the Models-3/Community Multiscale Air Quality (CMAQ) modeling system applied in East Asia and the northern China with the Multi-resolution Emission Inventory of China (MEIC) (Wang et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…Another simulation study suggested that these severe PM 2.5 episodes were driven by stable synoptic weather conditions rather than abrupt increase in anthropogenic emissions. Another modelling study over Hebei province found that external contributions of PM 2.5 in three heavily polluted cities may have originated from different areas, emphasizing the importance to establish a regional emission control framework (Wang et al, 2013a). However, none of these studies were designed to accurately estimate PM 2.5 concentration during this event.…”
Section: Introductionmentioning
confidence: 99%
“…The Group B cities are located in the most polluted city cluster, and emissions from this region are underestimated in the model. Similar to the GEOS‐Chem model, the regional‐scale Community Multi‐scale Air Quality model was found unable to reproduce the high PM 2.5 concentrations over Group B cities [ Wang et al ., ].…”
Section: Observed and Simulated Characteristics Of Pm25 During The Wmentioning
confidence: 99%